Leeches in the larynx - Kaygusuz, I; Yalçin, S; Keles, E (Springer-Verlag, 2001)
This is a report of four patients who inhaled leeches. They presented with severe attacks of inspiratory stridor, difficulty in breathing and spitting blood. Indirect laryngoscopy revealed a dark greenish living foreign body in the larynx in each case. Laryngoscopy was performed with local anaesthesia in two of the cases and general anaesthesia was used in the other two. The leeches were removed with forceps.
Keywords: larynx; leeches; foreign body; haemoptysis